Female thermal sensitivity and behaviour across the lifespan: A unique journey - Davide Filingeri; Hannah Blount; Alessandro Valenza (Experimental Physiology)
Abstract Women are a group of individuals that undergo unique anatomical, physiological and hormonal changes across the lifespan. For example, consider the impact of the menstrual cycle, pregnancy and menopause, all of which are accompanied by both short‐ and long‐term effects on female body morphology (e.g., changes in breast size) and temperature regulation, heat tolerance, thermal sensitivity and comfort. However, empirical evidence on how skin thermal and wetness sensitivity might change across the lifespan of women, and the implications that this has for female‐specific thermal behaviours, continues to be lacking. This paper is based on a symposium presentation given at Physiology 2023 in Harrogate, UK. It aims to review new evidence on anatomical and physiological mechanisms underpinning differences in skin thermal and wetness sensitivity amongst women varying in breast size and age, in addition to their role in driving female thermal behaviours. It is hoped that this brief overview will stimulate the development of testable hypotheses to increase our understanding of the behavioural thermal physiology of women across the lifespan and at a time of climate change.